Surgical management of neuroendocrine tumors. Issue 1 (January 2016) - Tamburrino, Domenico; Spoletini, Gabriele; Partelli, Stefano; Muffatti, Francesca; Adamenko, Olga; Crippa, Stefano; Falconi, Massimo
Abstract : During the last decades an increase in the incidence of neuroendocrine tumors (NETs) was observed. Gastroenteropancreatic NETs represent the majority of NETs. Compared with their epithelial counterpart they usually have a more indolent behaviour and surgical resection improves survival. Tumor diameter is one of the main parameter in the decision making process for nonfunctioning forms. Generally, small lesions can be treated conservatively whereas larger tumors should be treated with standard surgical resection and lymphadenectomy. Functioning tumors should be resected regardless the dimension of the lesion. Locally advanced and metastatic disease should be also treated with extended resections, keeping in consideration the grading, size, Ki67, and presence of extra-abdominal disease. In the case of metastases the panel of operative treatment includes resection, ablation, up to liver transplantation.